Second-degree superficial and second-degree deep burns, evolution with the use of amnion. Study to be carried out at Luis Vernaza General Hospital. (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
The following work is performed in order to identify and to show for all the people, the types of burns that occurs most often in our environment, as well as the various procedures used as a treatment in cases of burns of second surface level and deep. In this job we will focus on Amnios treatment and its evolution, for which they have taken data service Burned Luis Vernaza Hospital in the city of Guayaquil, in the period from January 2014 to December 2015, in order to analyze the problems described. The theoretical framework of this work has been developed with the following: anatomical General of the skin, skin physiology, burns, pathophysiology of burns, classification of burns, extent of burns, treatment, surgical methods and Amnios treatment. Patients were studied met the inclusion and exclusion criteria described in the job. The research results were analyzed and then processed statistically. The data were collected from medical records of patients through the HLV Servinter system.
Keywords: cause; burns; amnios; evolution; complications